Evaluating the growth and cost–benefit analysis of feeding improved indigenous chicken with diets containing black soldier fly larva meal - Waithaka, Mwangi K.; Osuga, Isaac M.; Kabuage, Lucy W.; Subramanian, Sevgan; Muriithi, Beatrice; Wachira, Ann M.; Tanga, Chrysantus M. (Frontiers in Insect Science, 2022)
The high cost of feeding is detrimental to the growth, sustainability and profitability of poultry production; hence alternative ingredients are being sourced to reduce this cost. Black Soldier Fly Larvae (BSFL) meal remains one of most promising alternative protein sources in animal feed globally. This study evaluated the growth performance of improved indigenous chicken (IIC) fed diets containing different inclusion levels of BSFL meals. BSFL meal inclusion rates were: 0% (Diet0), 5% (Diet1), 10% (Diet2), 15% (Diet3), and 20% (Diet4) to replace fishmeal in chick and grower diets. Diet type had significant effect on the average daily feed intake, feed conversion ratio, and average daily weight gain of the chicks. The average daily weight gain and feed conversion ratio, except average daily feed intake of the growers did not vary significantly variation across the various diets. The gross profit margin, cost benefit ratio and return on investment varied significantly across the different diets but was significantly higher when birds were fed Diet4. The highest benefit cost ratio of 2.12 was recorded in birds fed 20% BSFL meal inclusion diet and lowest of 1.76 from those fed 20% fishmeal inclusion diet. Our findings demonstrates that insect-based feeds can successfully and cost-effectively replace fishmeal up to 20% without compromising the growth performance of the birds. This implies BSFL meal could be incorporated as an essential part of on-farm feed production for IIC, with potential reduction in the total cost of feed, maintain optimal production and reduce the cost of chicken meat produced.